Solvent screening study of carbamazepine crystal polymorph - Muhamad Hadi, Sulaiman (2013)
Realizing solvents can be paramount critical and important in crystallizing specific polymorphs, complete manual, references, method and approach in predicting the polymorph formed from the specific parameter need to be developed. Solvent screening is the process of determining the relation between solvent choose and respective crystal form mainly focused on the solubility and its related properties. For this particular research, the approaches is by choosing specific properties of solvent used to find the relationship between them to relate with the crystallize structure formed. Polarity, hydrogen-donor-acceptor, and dipole moment is known to give much effect on the polymorph formation. By selecting the solvent with distinct properties considering its polarity, hydrogen-donor-acceptor, and dipole moment, the carbamazepine will be dissolve and recrystallize. Gravimetric method was used to determine the solubility of carbamazepine. DSC and optical microscopes was used to characterize the polymorph. Van `t Hoff plot was constructed from the solubility data and the stability prediction was made based on the free energy value calculated. It is found that weak interaction of solvent-solute will result in more stable polymorph but not necessarily correct because other factor such as temperature need to be consider during dissolution and crystallization process. One solvent having a tendency to produce more than one type of polymorph depend on the temperature of dissolution. Morphology of carbamazepine polymorph inconsistent for several trials and can be change easily through the process. This result will be potential additional reference for more perfect approaches in the future especially for molecular dynamic simulation.